Immobilization of Candida antarctica Lipase B on Fumed Silica - Cruz, Juan C.; Pfromm, Peter H.; Rezac, Mary E. (My University, 2009)
Enzymes are usually immobilized on solid supports or solubilized when they are to be used in organic solvents with poor enzyme solubility. We have reported previously on a novel immobilization method for s. Carlsberg on fumed silica with results that reached some of the best previously reported catalytic activities in hexane for this enzyme. Here we extend our method to Candida antarctica lipase B (CALB) as an attractive target due to the many potential applications of this enzyme in solvents. Our CALB/fumed silica preparations approached the catalytic activity of commercial Novozym 435 for a model esterification in hexane at 90wt% fumed silica (relative to the mass of the preparation). An intriguing observation was that the catalytic activity at first increases as more fumed silica was made available to the enzyme but then decreased precipitously when 90wt% fumed silica was exceeded. This was not the case for s. Carlsberg where the catalytic activity leveled off at high relative amounts of fumed silica. We determined adsorption kinetics, performed variations of the pre-immobilization aqueous pH, determined the stability, and applied fluorescence microscopy to the preparations. A comparison with recent concepts by Gross et al. may point towards a rationale for an optimum intermediate surface coverage for some enzymes on solid supports.
Keywords: CALB; Hexane; Enzyme immobilization; Fumed silica; Adsorption; Enzyme stability